Revision of the genus Symphytopria Kieffer (Hymenoptera, Diapriidae, Diapriinae) with notes on its taxonomy - Chemyreva, Vasilisa G. (Zootaxa, 2024)
The genus Symphytopria Kieffer, 1910 is revised based on an examination of the holotypes of all described species. Symphytopria fusciceps Kieffer, 1910, syn. nov. and S. nigroclavata Kieffer, 1910, syn. nov. are synonymized with Symphytopria fulva Kieffer, 1910; S. facialis Kieffer, 1910, syn. nov. is synonymized with S. trisulcata Kieffer, 1910. The male of S. fulva is described for the first time and illustrated. The generic diagnosis and the diagnosis of all included species is clarified. The tribal affiliation of this genus within the subfamily Diapriinae is discussed.